The Glypican proteoglycans show intrinsic interactions with Wnt-3a in human prostate cancer cells that are not always associated with cascade activation - de Moraes, Gabrielle Ferrante Alves (BMC Mol Cell Biol, 2021)
BACKGROUND: Prostate cancer occurs through multiple steps until advanced metastasis. Signaling pathways studies can result in the identification of targets to interrupt cancer progression. Glypicans are cell surface proteoglycans linked to the membrane through glycosylphosphatidylinositol. Their interaction with specific ligands has been reported to trigger diverse signaling, including Wnt. In this study, prostate cancer cell lines PC-3, DU-145, and LNCaP were compared to normal prostate RWPE-1 cell line to investigate glypican family members and the activation of the Wnt signaling pathway. RESULTS: Glypican-1 (GPC1) was highly expressed in all the examined cell lines, except for LNCaP, which expressed glypican-5 (GPC5). The subcellular localization of GPC1 was detected on the cell surface of RWPE-1, PC-3, and DU-145 cell lines, while GPC5 suggested cytoplasm localization in LNCaP cells. Besides glypican, flow cytometry analysis in these prostate cell lines confirmed the expression of Wnt-3a and unphosphorylated β-catenin. The co-immunoprecipitation assay revealed increased levels of binding between Wnt-3a and glypicans in cancer cells, suggesting a relationship between these proteoglycans in this pathway. A marked increase in nuclear β-catenin was observed in tumor cells. However, only PC-3 cells demonstrated activation of canonical Wnt signaling, according to the TOPFLASH assay. CONCLUSIONS: GPC1 was the majorly expressed gene in all the studied cell lines, except for LNCaP, which expressed GPC5. We assessed by co-immunoprecipitation that these GPCs could interact with Wnt-3a. However, even though nuclear β-catenin was found increased in the prostate cancer cells (i.e., PC-3, DU-145 and LNCaP), activation of Wnt pathway was only found in PC-3 cells. In these PC-3 cells, GPC1 and Wnt-3a revealed high levels of colocalization, as assessed by confocal microscopy studies. This suggests a localization at the cellular surface, where Frizzled receptor is required for downstream activation. The interaction of Wnt-3a with GPCs in DU-145 and LNCaP cells, which occurs in absence of Wnt signaling activation, requires further studies. Once non-TCF-LEF proteins can also bind β-catenin, another signaling pathway may be involved in these cells with regulatory function. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12860-021-00361-x.